INTERNET MEMES AS A MEANS OF VISUAL COMMUNICATION - Melkonyan, Nvard; Karaperyan, Anna (Journal of Sociology: Bulletin of Yerevan University, 2019)
Today Internet memes have a special role in the process of organizing visual communication. Internet memes are based on the visual perception of people and are designed to describe and interpret certain situations in social life. In our society Internet memes are widely used by social network users. Their specificity and uniqueness are due to the mechanisms of their formation, actualization, and distribution. In modern science, the study of Internet memes as an effective means of visual communication is considered to be highly relevant.